Centre For Graduate Studies: Graduate Programmes: 2001 2002/ Centre for Graduate Studies, UiTM - UiTM, Centre for Graduate Studies (Centre for Graduate Studies, UiTM, 2001)
The Centre for Graduate Studies, established in April 1997, is aimed at providing opportunities for Bumiputera graduates to further their education at master's and doctoral levels. The Centre operates as a one-stop centre for postgraduate applications. It coordinates and determines policies on admission and academic regulations and also provides support to facilitate learning. The Centre's mission is to nurture the creation of a graduate learning community that constantly explores all forms and types of knowledge to push its frontiers through basic and applied courses for societal well being. The Centre's vision is to be at the forefront of graduate academic advancement as well as professional application premised on a global outlook and interdisciplinary synergism.